THU0585 The patient's university - an innovative concept in the education of patients with rheumatoid arthritis - Rodriguez, F; Villarreal, L; Santos-Moreno, P; Cabrera, M; Buitrago-Garcia, D; Caicedo, C (Annals of the rheumatic diseases, 2017)
BackgroundRheumatoid arthritis (RA) is a chronic, inflammatory autoimmune disease of unknown etiology, it is a long term condition that causes pain, disability and affects the quality of life (1). In another countries has been demonstrated how patient education can empower the individual giving as a result a better decision making between the practitioner and patient in order to obtain better health care outcomes compared to patients that are not involved in educational activities (1).ObjectivesThe objective of this work is to show how through a progressive program of patient education we reach the concept of the “expert patient” and the “patients' university”.MethodsWe performed a systematic review of the literature in global and regional databases (Pubmed, Medline, Scopus, Lilacs), in order to search for information on this research question-hypothesis. Subsequently and under a Delphi-modified methodology and consensus of experts lay the conceptual bases on this particular subject – patient's education in rheumatic disease. As a result of the above was defined a proposal for the constitution and development of the program of patient's education in a RA specialized center under the concept of the “expert patient” (EP) and the “patients' university”(PU).ResultsFrom conceptual point of view specific themes regarding patient's education were developed by a coordinator who, after a review of the literature, presented a specific proposal on the particular topic that was discussed with the panel members and then voted on and finally implemented within the EP y PU concepts. In a specialized RA center in Bogotá Colombia during 2016 we started a patient and caregiver oriented program to support the clinical treatment in patients with RA. The structure of the program was an educational-recreational strategy where we integrated health education (disease activity, pharmacovigilance, psychology and nutrition) and recreational activities such as crafts, yoga, aerobics and dance lessons with a periodicity of two times per week. We called the program “Gest-Art”. As a result of this pilot program we obtained a positive impact and perception among patients and care takers; we had the participation of 600 people during the whole year. The next phase is to develop a step-by-step program to initially train and then specialize patient focus groups (expert patient); and later develop a model of continuous improvement (updating) that we will call the university of patients.ConclusionsFrom this experience we can conclude that the implementation of this educational program opened the opportunity to empower and motivate our patients and caregivers to be actively participative with the disease management and health care, also the program has been a space for the patients to share their experiences and to propose new strategies to improve the program.References Prothero L, Georgopoulou S, de Souza S. Patient involvement in the development of a handbook for moderate rheumatoid arthritis. 2016. Disclosure of InterestNone declared